POTENSI KEJADIAN ROB DI PESISIR PROBOLINGGO SERTA PERBANDINGAN KONDISINYA ANTARA MUSIM BARAT DAN MUSIM TIMUR BERDASARKAN DATA OSEANOGRAFI DAN METEOROLOGI - Asep Sandra Budiman; Indarto Happy Supriadi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Tidal flood has become a serious problem in several coastal areas in Indonesia, particularly in Probolinggo, East Java Province - Indonesia. The study of tidal flood in the coastal area of Probolinggo was conducted by processing and analyzing oceanographical and meteorological data to asses the possibility and to compare its variability between the West and East seasons. Data is used for this study consist of tidal and wind data from Stamet II Perak Surabaya (7 years from 2004 - 2011); rainfall data from BMKG Juanda Surabaya (9 years from 2002 - 2011); and Probolinggo topography data from SRTM (Shuttle Radar Topography Mission - http://srtm.csi.cgiar.org/). Tidal flood occurrence possibility was determined by comparing the sea level heights with the topography of the study area. the meteorological data were analyzed to compare its variability during West and East seasons. Results show that tidal flood may occur at several points on the coast of Probolinggo while the high tide occurs especially during the spring tide since the sea level was higher (0.73 m) than the topography of the coastal area of Probolinggo (<0.5 m by average). The condition becomes worse during the East season due to the existence of strong wind in the direction that contributes to generating a high wave in the coastal.